Observing Strategies in Intercomprehension Reading. Some Clues for Assessment in Plurilingual Settings - Bonvino, Elisabetta; Fiorenza, Elisa; Cortés Velásquez, Diego (Frontiers in Communication, 2018)
The practice of teaching intercomprehension (IC) aims to promote plurilingualism in the individual and maintain language policies supporting multilingualism. It proposes a communicative model in which people communicate using their own language by encouraging the development of the competences required for successful communication. Most of the projects on IC that have been developed in recent years target developing written comprehension, especially among Romance languages. Although there is great diversity in objectives and techniques, all methodologies based on IC share the following principles, which represent the common denominator of teaching IC: plurilingual approach, use of partial competences, attention to comprehension, reflection on language(s), development of strategic and metacognitive knowledge and competences. Most of the teaching paths based on IC aim to raise learners’ awareness of comprehension processes, therefore allowing students to develop specific strategies connected with analogy, approximation (or ‘ambiguity tolerance’), association, transfer, inference and metalinguistic knowledge. One of the main challenges of IC studies is to describe the individual competences that allow people to understand – or to learn to intercomprehend– texts in several related languages. Such a description would allow us to propose reflections in order to elaborate an assessment tool. The assessment in IC has been focused by several works, it is the main objective of the European Project EVAL-IC (Evaluation des compétences en intercomprehénsion: réception et interactions plurilingues) and is certainly crucial for the institutional insertion. The objective of this paper is to present, within the topic of IC, some insights gathered by the authors through the EuRom5 methodology. In particular, we focus on the subtopic of the use of strategies as observed during EuRom5 sessions putting them in relation to the descriptors of different frameworks of reference related to plurilingualism (MAGIC, CARAP, REFIC and New CEFR). As for the methodology adopted in this paper, we propose a description and a comparison of data from EuRom5 and the frameworks mentioned above. The main findings of our analysis show that the four frameworks here considered only partially account for the complex picture characterizing the EuRom methodology.